Literary Translation and Elimination of the Soviet Ideology in Contemporary Ukraine - Rudnytska, Nataliia (2023)
De-Sovietization became an important issue of the post-Soviet Ukrainian agenda, and the Russo-Ukrainian war gave a strong impetus to it. The subject matter of the present study is the instrumentality of literary translation in eliminating the Soviet ideology in independent Ukraine. The research is made within the sociological approach, which allows to describe the specific features of the sphere of literary translation, influenced by the sociopolitical and ideological factors. The research material includes the data on the translated texts published in contemporary Ukraine in the state bibliographical index and the catalogues of the leading Ukrainian publishers of foreign literature as well as para- and metatexts (translators and editors’ commentaries, interviews and publications in media).
Keywords: literary translation; de-Sovietization; ideology; censorship; totalitarianism